A clinical study on retinopathy of prematurity in a tertiary care centre - Dalai, Ramamani; Das, Kedarnath; Nayak, Diptimayee; Murmu, Mangal Charan; Nanda, Prasanta Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Retinopathy of prematurity (ROP) is a multifactorial vasoproliferative retinal disorder that increases in incidence with decreasing gestational age. India shares 20% of the world childhood blindness. Besides congenital cataract, congenital glaucoma and ocular injuries, ROP is emerging as one of the important causes of childhood blindness in India. Methods: This hospital based prospective study was undertaken during October 2016 to September 2018 in the Department of Ophthalmology, SCB Medical College. Authors included (a) all preterm infants weighing less than 1750gm or gestational age less than 34 weeks at birth, (b) infants with birth weight between 1750gm to 2000gm and gestational age more than 34 weeks (late preterm and term infants) those were considered as high risk. Results: Among the 328 babies included in our study, the incidence of ROP was 29.57%. Bilateral ROP was found in 76.29% with nearly equal stages in both eyes and only 23 neonates showed unilateral involvement. Conclusions: Low birth weight, lower gestational age, blood transfusion, Respiratory Distress Syndrome (RDS), apnoea, supplemental oxygen therapy, maternal anaemia and gestational diabetes mellitus (GDM) were strongly associated with development of ROP.